A Hungarian rhapsody in lipids. (April 2013) - Moriarty, Patrick M
The first World Congress of Clinical Lipidology in Budapest, Hungary was attended by research scientists and clinicians from around the world who sought to further their understanding of lipid disorders. Research on a wide range of topics in the field of lipid disorders was presented and provoked important discussions and questions among attendees. In lectures, plenary sessions, workshops and poster sessions, numerous topics from diagnosis to treatment, diet to novel lipid-lowering drugs, adverse events to issues of compliance, and a host of other topics were discussed.The combination of experiencing the richness of Budapest's culture, history and beauty, and the thought-provoking and exciting research and discussions that engaged those attending the conference resulted in a highly rewarding experience both educationally and culturally.